How does foreign direct investment really affect developing countries' growth? - Dierk Herzer (Georg-August-Universität Göttingen, Ibero-America Institute for Economic Research (IAI), 2010)
This paper contributes to the literature on foreign direct investment (FDI) and economic growth in two main ways. First, we examine the effect of FDI on economic growth for 44 developing countries over the period 1970 to 2005 using heterogeneous panel cointegration techniques that are robust to omitted variables and endogenous regressors. In contrast to previous studies, we find that FDI has, on average, a negative effect on growth in developing countries, but that there are large cross-country differences in the growth effects of FDI. Second, we use a general-tospecific model selection approach to systematically search for country-specific factors explaining the cross-country differences in the growth effects of FDI. Contrary to previous results, we find that the cross-country differences in per capita income, human capital, openness, and financial market development cannot explain the cross-country differences in the growth effects of FDI. Instead, the growth effects of FDI are positively related to freedom from government intervention and freedom from business regulation, and negatively related to FDI volatility and natural resource dependence.
Keywords: F21; F43; C23; C21; 330; FDI; Growth; Developing countries; Panel cointegration; General-to-specific approach; Direktinvestition; Wirtschaftswachstum; Entwicklungsländer